The HUMAINE Database: Addressing the Collection and Annotation of Naturalistic and Induced Emotional Data - Douglas-Cowie, Ellen; Cowie, Roddy; Sneddon, Ian; Cox, Cate; Lowry, Orla; McRorie, Margaret; Martin, Jean-Claude; Devillers, Laurence; Abrilian, Sarkis; Batliner, Anton; Amir, Noam; Karpouzis, Kostas (Affective Computing and Intelligent Interaction, 2007)
The HUMAINE project is concerned with developing interfaces that will register and respond to emotion, particularly pervasive emotion (forms of feeling, expression and action that colour most of human life). The HUMAINE Database provides naturalistic clips which record that kind of material, in multiple modalities, and labelling techniques that are suited to describing it.